Image Processing in Repairing the Red Zone of Vehicle Barriers in Binjai City with Edge Detection Algorithm - Sidi Uzayva Resyad (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Red zones on road markings are an important element in the traffic system that serves as a barrier or prohibition on stopping, parking, or crossing certain areas. In Binjai City, red zones are commonly found at intersections, near zebra crosses, or busy areas such as markets and schools. However, in its implementation in the field, the effectiveness of red zones is often not optimal due to various obstacles. In addition, "manual surveillance of red zone conditions" requires large human resources and has not been able to reach all vulnerable points effectively. Regular checks and maintenance efforts are often hampered by time and budget constraints. As a result, some red zone points are damaged or lost unnoticed for a long time. This study aims to design and test image processing methods with edge detection algorithms in detecting and improving the appearance of traffic red zones in Binjai City. It is hoped that this solution can increase the effectiveness of traffic supervision and support efforts to control highways in a more modern and efficient manner. The result of the calculation above is a binner image with the number 0 being the color that shows black and the number 1 is the color that shows white. Showing the image is the result of a black and white image process. So from the calculation above, there is a Sobel algorithm that calculates the final value of the higher calculation is the Sobel algorithm with the level of fineness and clarity in the image.